SOLAR FUEL’S ENERGY EFFICIENCY ESTIMATION OF RICE MILLING FACTORY WITH LEVEL VARIATIONS - Indriyani -; M Yunus; Wisnaningsih -; Ruslan Dalimunthe (Prosiding International conference on Information Technology and Business (ICITB), 2017)
In order to reach out to the people of this country, they had been able to use the milling of the solar panels, but they did not have enough solar energy. It needed fuel was very variation at each level of Rice Milling Factory (RMF) such as were Small Capacity of Rice Milling Factory (SCRMF), Medium Capacity of Rice Milling Factory (MCRMF), and Big Capacity of Rice Milling Factory (SCRMF). In this research consisted of 3 levels and 9 samples, there were 3 samples of  Small Capacity of Rice Milling Factory (SCRMF), 3 samples of Medium Capacity of Rice Milling Factory (MCRMF), and 3 samples of Big Capacity of Rice Milling Factory (SCRMF). The research system took a research for one year. In order to achieve the highest level of fuel.  The MCRMF was being used efficient for the purpose of solar energy. In the current year, MCRMF has been used of solar fuel to 9.30 liters per hour per 0.60 ton of rice products, SCRMF of solar fuel to 13.97 liters per hour per 1.00 ton of rice products, BCRMF of solar fuel to 18.02 liters per hour per 2.00 tons of rice products. Keywords: Solar fuel, energy efficiency, Rice Milling Factory (RMF), Small Capacity of Rice,                       Milling Factory (SCRMF), Medium Capacity of Rice Milling Factory (MCRMF), Big Capacity of Rice Milling Factory (BCRMF), rice products.